The role of emotions on pacing strategies and performance in middle and long duration sport events. Issue 6 (23rd June 2009) - Baron, B; Moullan, F; Deruelle, F; Noakes, T D
Abstract : Thepacing strategy may be defined as the process in which the total energy expenditure during exercise is regulated on a moment-to-moment basis in order to ensure that the exercise bout can be completed in a minimum time and without a catastrophic biological failure. Experienced athletes develop a stable template of the power outputs they are able to sustain for different durations of exercise, but it is not known how they originally develop this template or how that template changes with training and experience. While it is understood that the athlete's physiological state makes an important contribution to this process, there has been much less interest in the contribution that the athlete's emotional status makes. The aim of this review is to evaluate the literature of physiological, neurophysiological and perceptual responses during exercise in order to propose a complex model interpretation of this process which may be a critical factor determining success in middle- and long-duration sporting competitions. We describe unconscious/physiological and conscious/emotional mechanisms of control, the focus of which are to ensure that exercise terminates before catastrophic failure occurs in any bodily system. We suggest that training sessions teach the athlete to select optimal pacing strategies by associating a level of emotion with the ability to maintain that pace for exercise of different durations. That pacing strategy is then adopted in future events. Finally, we propose novel perspectives to maximise performance and to avoid overtraining by paying attention also to the emotional state in training process.